CAR-T cell therapy: developments, challenges and expanded applications from cancer to autoimmunity - Yaojie Kong; Jingyao Li; Xueyao Zhao; Yanwei Wu; Liang Chen (Frontiers in Immunology)
Chimeric Antigen Receptor (CAR)-T cell therapy has rapidly emerged as a groundbreaking approach in cancer treatment, particularly for hematologic malignancies. However, the application of CAR-T cell therapy in solid tumors remains challenging. This review summarized the development of CAR-T technologies, emphasized the challenges and solutions in CAR-T cell therapy for solid tumors. Also, key innovations were discussed including specialized CAR-T, combination therapies and the novel use of CAR-Treg, CAR-NK and CAR-M cells. Besides, CAR-based cell therapy have extended its reach beyond oncology to autoimmune disorders. We reviewed preclinical experiments and clinical trials involving CAR-T, Car-Treg and CAAR-T cell therapies in various autoimmune diseases. By highlighting these cutting-edge developments, this review underscores the transformative potential of CAR technologies in clinical practice.